Proposing Fuzzy Bow-Tie Method for Assessment of Occupational Risks at Shipyards - Cebi, Selcuk; Ilbahar, Esra (CHAMBER MARINE ENGINEERS, 2018)
Production in the shipyards is considered as heavy industrial production, and majority of ship production is still performed in the form of project type production. Ship building is one of the riskiest regarding its activities and working conditions. The numbers of the occupational accidents and the results of the occupational injuries prove that urgent precautions should be taken for ship building industry. In this paper, an integrated risk assessment method including fuzzy sets, rule based inference system, analytic hierarchy process, and Bow-tie technique has been proposed to literature in order to consider and reduce occupational risks at shipyards. Bow-tie technique is widely preferred to use in analysis of occupational risks at workplace. This method is used in analyzing both the key factors that cause a risk to occur and the consequences of a risk. In the scope of this study, unlike the literature, the bow tie technique has been combined with the fuzzy inference system. When an accident takes place, there are likely to be various different outcomes, and it results in only one of these outcomes. However, the current risk assessment methods only consider the severity of the most likely outcome to predict risk magnitude. In this paper, as different from the currently used methods, the magnitudes of occupational risks are obtained by considering all the possible outcomes of a potential accident. The proposed approach has been applied for ship building process to rank risky acitivities, and preventive measures have been proposed to reduce risk levels.
Keywords: Risk Analysis; Bow-tie Technique; Fuzzy Logic; Fuzzy Inference System; Engineering; Transportation